2021
DOI: 10.1002/ijc.33696
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab in combination with 5‐fluorouracil, leucovorin, oxaliplatin and docetaxel as perioperative treatment for patients with human epidermal growth factor receptor 2‐positive locally advanced esophagogastric adenocarcinoma: A phase II trial of the Arbeitsgemeinschaft Internistische Onkologie Gastric Cancer Study Group

Abstract: Perioperative chemotherapy with 5-fluorouracil, leucovorin, oxaliplatin and docetaxel (FLOT) is a mainstay in the treatment of esophagogastric adenocarcinomas (EGA).Trastuzumab improved survival when added to chemotherapy in patients with HER-2-positive metastatic EGA. We investigated the combination of trastuzumab and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 22 publications
(40 reference statements)
1
52
0
4
Order By: Relevance
“…[25] However, a phase II study observed one severe cardiac disorder, potentially attributable to the addition of trastuzumab to FLOT. [17] The pathological complete response (pCR) rate was 16% (range 9.6-22.2%) in three studies. [16][17][18] On the other hand, no survival benefit was demonstrated with the addition of trastuzumab to six weeks of chemoradiotherapy in preliminary results of a large randomized study (n=203).…”
Section: Single Her2 Targeting With Trastuzumabmentioning
confidence: 95%
See 4 more Smart Citations
“…[25] However, a phase II study observed one severe cardiac disorder, potentially attributable to the addition of trastuzumab to FLOT. [17] The pathological complete response (pCR) rate was 16% (range 9.6-22.2%) in three studies. [16][17][18] On the other hand, no survival benefit was demonstrated with the addition of trastuzumab to six weeks of chemoradiotherapy in preliminary results of a large randomized study (n=203).…”
Section: Single Her2 Targeting With Trastuzumabmentioning
confidence: 95%
“…The included studies demonstrated feasibility of the addition of trastuzumab to conventional cytotoxic therapy. [16][17][18]23,25] No increase in treatment-related toxicities, as well as no unexpected safety findings were observed by adding trastuzumab to the treatment regimens. [16][17][18]25] Two studies reported relatively high incidences of grade ≥3 diarrhea (33%) and neutropenia (28%), although toxicities were manageable.…”
Section: Single Her2 Targeting With Trastuzumabmentioning
confidence: 97%
See 3 more Smart Citations